2017
DOI: 10.1007/s11306-017-1186-y
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induces a shift in lipid and primary carbon metabolites in a model of fasting-induced insulin resistance

Abstract: Introduction Prolonged fasting in northern elephant seals (NES) is characterized by a reliance on lipid metabolism, conservation of protein, and reduced plasma insulin. During early fasting, glucose infusion previously reduced plasma free fatty acids (FFA); however, during late-fasting, it induced an atypical elevation in FFA despite comparable increases in insulin during both periods suggestive of a dynamic shift in tissue responsiveness to glucose-stimulated insulin secretion. Objective To better assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 74 publications
3
11
0
Order By: Relevance
“…Our results therefore reveal a previously unknown feature of the insulin resistance in hibernating bears, namely, that it progressively increases throughout hibernation. A similar progressive change has been observed in elephant seal pups over several months of fasting (Olmstead et al, 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Our results therefore reveal a previously unknown feature of the insulin resistance in hibernating bears, namely, that it progressively increases throughout hibernation. A similar progressive change has been observed in elephant seal pups over several months of fasting (Olmstead et al, 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Despite this contradictory evidence, the metabolomics data suggests that ketogenesis is suppressed suggesting that in fasting seal pups, insulin out-competes glucagon for the regulation of ketogenesis. This is further substantiated by previous studies that demonstrate that: 1) insulin infusion in fasting seal pups suppresses b-hydroxybutyric acid (17) and 2) the natural increase in ketones ( 8) is associated with reduced insulin (31,33).…”
Section: Glp-1 Suppresses Amino Acid Catabolism and Ketogenesis Relative To Controlsupporting
confidence: 68%
“…However, reductions in plasma levels do not necessarily imply a state of nonfunctionality. For example, despite the fasting-induced reductions in insulin, we have demonstrated that exogenous insulin infusion in late-fasted seal pups (when levels are the lowest) induced time-dependent changes in the phosphorylation of insulin receptor and downstream signaling proteins in adipose and muscle (although the cellular signaling events were suppressed compared with early-fasted pups in the same study) (7) and in the metabolome (17) suggesting that the tissues remain insulin sensitive. Given that GLP-1 facilitates GSIS and induces GLP-1 receptor-mediated cellular effects independent of insulin, we took a similar approach as with insulin and have shown that exogenous GLP-1 in late-fasted seal pups induced profound changes in their hormone profile and time-dependent changes in insulin receptor phosphorylation, again suggesting that tissues remain responsive to GLP-1 (7).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Of particular interest will be the utilization of combined next-generation approaches [e.g. transcriptomics (Khudyakov et al, 2015a,b) proteomics, phosphoproteomics and metabolomics (Olmstead et al, 2017); reviewed in Ng'oma et al, 2017] in future studies, as these will provide a clear picture of the molecular mechanisms underlying starvation responses. Combined next-generation studies have been used in many systems to more precisely establish critical biological responses through identification of enriched pathways overlapping between methods (e.g.…”
Section: Mechanisms Responses and Traits Affected By Repeated Starvamentioning
confidence: 99%